Combined and Substituted Use of Battery Electric Vehicles and Hydrogen in Nanogrid Configurations - Dahiru A.T.; Tan C.W.; Lau K.Y.; Rosmin N.; Ibrahim O.; Toh C.L. (Institute of Electrical and Electronics Engineers Inc., 2025)
Renewable energy systems consider energy storage against uncertainties of weather resources and customer demands. Battery energy storage dominates recent renewable energy-based system developments. Factors for the battery dominance include the extended life-cycle, high energy density and low per unit kWh cost. However, hydrogen storage had a significant drop in per kWh cost and longer periods of energy storage. Electric vehicles have a high percentage of lifespan spent parking implying low energy storage usage. This paper investigates the technoeconomics of a residential nanogrid's energy storage system configured using battery, electric vehicles and hydrogen fuel cells. The Photovoltaic/Wind/Storage nanogrid configurations were optimized using nested integer linear programming with energy storage planned in combined and substituted modes for cost/capacity benefits. The nanogrid's energy costs in substituted storage were 44%, 22% and 39% in battery, electric vehicles and hydrogen storage lower than the combined storage's 0.0018 $/kWh. The substituted storages are 30%, 24% and 44% lower than the combined storage's $111,330 annualized total cost. However, hydrogen storage's 65 kW capacity is larger compared to electric vehicle's 55 kW and battery's 50 kW. Electric vehicles are envisaged to have better economic advantages under optimal load management. ? 2024 IEEE.